Flow structure of a quasi-stationary jet in the western subarctic Pacific (the Western Isoguchi Jet). (August 2020) - Wagawa, Taku; Ito, Shin-ichi; Kakehi, Shigeho; Shimizu, Yugo; Uehara, Kazuyuki; Kuragano, Tsurane; Nakano, Toshiya
Abstract: The Western Isoguchi Jet, a quasi-stationary baroclinic jet that separates from the Kuroshio Extension, has been detected for a decade. Here we report the first observations of the vertical structure and temporal variations of the jet via moored current meters (September 2011–September 2012) and intensive hydrographic measurements (September 2010, 2011, and 2012). The jet flows northeastward and supplies subtropical water (northeastward velocity was ∼ 0.16 m s −1 and temperature was ∼ 4.4 ° C at 300 m depth, and they were ∼ 0.05 m s −1 and ∼ 2.9 ° C at 1000 m depth). We newly estimated the volume, heat, and salt transports of the jet to be 13.6–26.5 Sv, 0.0745–0.173 PW (reference potential temperature of 4.0 ° C ), and 5.58–9.91  ×  10 6  kg s −1 (reference salinity of 33.5), respectively. Year-to-year changes of the jet axis complicated its horizontal distribution. The jet flowed stably northeastward throughout the year with weak seasonal variability. The vertical structure of the jet is quite different from that of the surrounding flow. These observations are consistent with the mechanism proposed by Mitsudera et al. (2018) and Miyama et al. (2018) to be responsible for the formation and maintenance of the jet. Highlights: The first observations of the Western Isoguchi Jet via moored current meters measurements were made. The volume, heat, and salt transports of the jet were newly estimated. The jet flowed stably northeastward throughout the year. The jet had a surface-intensified vertical structure.